Research on topology control in WSNs based on complex network model - Chuanyun Wang; Yin Yan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexA topology control algorithm based on mutual selection mechanism is proposed, combined with complex network model. It adopts node strength and spacing between nodes as the measuring parameters, selects the cluster head nodes based on mutual selection mechanism in the communication radius of nodes and builds the hierarchical topology. The algorithm can improve the clustering efficiency, shorten the average path length, save the energy of the nodes. The simulation and analysis of network evolving process and algorithm model are completed using MATLAB tools and the results verify the correctness and stability of the proposed algorithm model. The algorithm is suitable for large-scale node deployment in WSNs.